After the Cold War: Does international trade and financial law matter? - Breskovski, Vassil (European University Institute, 1998)
Keywords: Cold War; Commercial law; Foreign economic relations; International Trade; International business enterprises; International economic relations; Post-communism; Russia (Federation)

States and markets : regulatory competition and the public law of banks - Padrós Reig, Carlos (European University Institute, 1997)
One of the most immediate questions that could be raised is that of the topic. Why banks?. Banks are a part of the economy which is especially prone to regulatory competition. Increasing financial globalization makes it difficult to maintain regulatory barriers and those remaining create costs that are avoided by regulatory arbitrage. Banks’ raw material is capital which is a highly mobile element. On the top of that, the longstanding experience of the US in the field, should be of some usefulness. Finally, banks are attractive since the European Union, by means of the Second Banking Directive, has undertaken a decisive step towards liberalisation. Regulatory competition in this field will be able to give us some clues into the direction of services regulation in general, and into the new institutional dimension of the Union. However, banks are only one type of financial actors. Securities and insurance industry are gradually occupying spaces traditionally reserved to banks - namely deposit collection and lending - and conversely, banks are extending their product range to cover securities and insurance activities, and are experiencing a process of disintermediation. Hence, it is increasingly impossible to distinguish among financial actors. Concentrating in one of them is just a research need in order to keep the study under manageable dimension. Still, banks remain a legally different industry because of their position in the economic gear and in the payment system. What could actually be questioned is the future of banks themselves or at least their different legal treatment In any case, the topic of financial services regulation is too large to be covered as a whole, so some subdivision is necessary. This has to be done acknowledging that divisions may not correspond to the reality of the marketplace.
Keywords: Banks; Competencia; Competition law; Law of Banks; Regulation

Two essays on political influence and the regulation of financial markets - Eckel, Doug (Virginia Tech, 1996)
I examine two potential instances of rent-seeking in financial markets in the 1980s. In the first essay I test whether managers engage in political activity designed to influence federal regulation of the market for corporate control. In the second, I examine whether firms in the financial services sector attempt to affect bank deregulation. Using Federal Election Commission data, I find campaign contributions by corporate political action committees (PACs) are negatively related to levels of inside ownership, my main proxy for managerial vulnerability to hostile tender offers. Contribution patterns for firms with less than 20% insider ownership are relatively highly correlated, and differ from those of firms with greater than 20% inside ownership. Low inside ownership firms have slightly higher levels of contributions to legislators on particular House and Senate committees proposing relevant legislation. However, when I analyze the impact of contributions on legislator support for regulation I find no statistical support for a theory of vote-buying. I conclude that corporate political behavior is tied to levels of inside ownership, and comprises an alternate index of manager-shareholder conflict. Using a similar approach to analyse the financial services industry, I also find significant patterns in political action committee (PAC) campaign contributions for depository (commercial bank and thrift) and non-depository (brokerage and insurance) sectors of the financial services industry during the 98th Congress (1983-84). Contributions by depository firm PACs appear not only to purchase access to legislators serving on important banking committees crucial to their interests, but are also a significant determinant of votes for repealing sections of the Glass-Steagall Act. Nondepository contributions do not appear to influence votes directly, even though the brokerage and insurance sectors effectively lobbied House Banking Committee chairman Fernand St Germain to enforce the regulatory status quo. When I measure the rents at stake in the legislation using a two-factor market model event study approach, I find that the passage of legislation in the Senate had a positive affect on depository firm returns, implying the sector's lobbying effort was justified. However non-depository PACs lobbied just as extensively, and did not experience significant abnormal returns over the same event period, even though this round of deregulation should have been a zero-sum game between the affected sectors of the industry. I then measure the correlation between the market value impacts of new legislation and contribution amounts for individual firms within the sectors. I find rents are correlated with political activity, even for firms in the non-depository sectors.
URI: http://hdl.handle.net/10919/39160
Keywords: Corporate control; Financial institutions; Financial markets; Regulation